Structural vs. relational embeddedness: social capital and managerial performance - Moran, Peter (Strategic Management Journal, 2005)
Abstract This paper examines the impact of managers' social capital on managerial performance. Two dimensions of social capital are compared—the structural embeddedness (i.e., configuration) of a manager's network of work relations and the relational embeddedness (i.e., quality) of those relations. Based on a sample of 120 product and sales managers in a Fortune 100 pharmaceutical firm, this paper presents evidence indicating that both elements of social capital influence managerial performance, although in distinct ways: structural embeddedness plays a stronger role in explaining more routine, execution‐oriented tasks (managerial sales performance), whereas relational embeddedness plays a stronger role in explaining new, innovation‐oriented tasks (managerial performance in product and process innovation). This research considers resource exchanges within firms as key to value creating behaviors and contributes a deeper understanding of how social capital influences productive resource exchanges. Copyright © 2005 John Wiley & Sons, Ltd.